Gender role in agroforestry of areca nut and coffee in peatland area: Case of Jambi Province, Indonesia - Lestari, Sril (Ministry of Environment and Forestry, Indonesia, 2019)
Presented by Sril Lestari (Ministry of Environment and Forestry of Indonesia), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.